2009
DOI: 10.1016/j.bpj.2008.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Ceramide-1-Phosphate at the Air-Water Solution Interface in the Absence and Presence of Ca2+

Abstract: Ceramide-1-phosphate, the phosphorylated form of ceramide, gained attention recently due to its diverse intracellular roles, in particular in inflammation mediated by cPLA(2)alpha. However, surprisingly little is known about the physical chemical properties of this lipid and its potential impact on physiological function. For example, the presence of Ca(2+) is indispensable for the interaction of Cer-1-P with the C2 domain of cPLA(2)alpha. We report on the structure and morphology of Cer-1-P in monomolecular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 52 publications
4
34
0
Order By: Relevance
“…It is worth noting that the C s −1 values for the S phase of pCer found here are similar to those of the solid phase state of fatty acids and cholesterol (Davies and Rideal, 1963;Smaby et al, 1997) and are higher than the C s −1 values reported for other phospholipids or sphingolipids with the only exception of galactosylceramide with saturated fatty acyl chains (Smaby et al, 1996). By contrast, the C s −1 values found for the LC phase of pCer is rather similar to that reported for natural Cer (Maggio, 2004) and Cer-1 phosphate (Kooijman et al, 2009). Further features of this diffuse phase transition are provided by isobars analysis (see below).…”
Section: Resultssupporting
confidence: 61%
“…It is worth noting that the C s −1 values for the S phase of pCer found here are similar to those of the solid phase state of fatty acids and cholesterol (Davies and Rideal, 1963;Smaby et al, 1997) and are higher than the C s −1 values reported for other phospholipids or sphingolipids with the only exception of galactosylceramide with saturated fatty acyl chains (Smaby et al, 1996). By contrast, the C s −1 values found for the LC phase of pCer is rather similar to that reported for natural Cer (Maggio, 2004) and Cer-1 phosphate (Kooijman et al, 2009). Further features of this diffuse phase transition are provided by isobars analysis (see below).…”
Section: Resultssupporting
confidence: 61%
“…This tilting facilitates formation of stable H-bonds between cationic residues and the C1P headgroup. This observation is further supported by the fact that the C1P headgroup is much smaller in size than the POPC headgroup and is thought to be more deeply buried, and at physiological pH, the C1P acyl chains have been found to tilt away from the surface normal of the monolayer ( 56 59 in Fig. 7B ), which has previously been shown for Lys and Arg residues in peptides that bind PA ( 57 ).…”
Section: An Experimental Analysis Of Cpla 2 ␣ -C2 and C1p Interactionssupporting
confidence: 67%
“…Because the translocation of cPLA 2 ␣ was signifi cantly Now that we have shown the origin of C2 domain C1P binding, it is important to ask how this domain is able to locate a membrane-embedded C1P molecule. Previous studies have demonstrated that owing to its small phosphomonester headgroup, C1P would be slightly buried and also tilted in a membrane at physiological pH ( 56 ). Because cPLA 2 ␣ -C2 binds to PC membranes in a Ca 2+ -dependent manner, we hypothesize that this docking serves to allow the protein to sample the membrane for C1P.…”
Section: The C2 Domain Tilts Toward the Membrane To Bind C1pmentioning
confidence: 84%
“…First, C-1-P and PA have different pK a values of the phosphomonoester headgroup (57,58) that may elicit a larger anionic charge on C-1-P (Ϫ2) in DOPE and DOPC membranes. Additionally, 0.5-1 Ca 2ϩ ions have been found to bind to each C-1-P molecule in a model membrane (59), which could suggest a Ca 2ϩ -bridging model between annexin a2 and C-1-P in membranes.…”
Section: Discussionmentioning
confidence: 89%